ØªØ£Ø«ÙŠØ± Ø¥Ø³ØªØ®Ø¯Ø§Ù… Ø§Ù„ØºÙ†Ø§Ø¡ Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø¹Ù„Ù‰ ØªØØ³ÙŠÙ† Ù…Ù‡Ø§Ø±Ø© Ø§Ù„Ø¥Ø³ØªÙ…Ø§Ø¹ - asriandi asriandi (Lughatu Ad-Dhat, 2020)
ABSTRACT Research objectives: To find out the effect of using Arabic singing on improving the listening skill of students of the tenth semester of the secondary school Nahdet Al-Watan Franjasila. How did the use of Arabic singing affect the improvement of the listening skill of the tenth class students between the experimental class and the control class in the secondary school Nahdet Al Watan Franjasila. As for the research method, which uses quantitative and experimental methods. The research design used is a quasi-experimental design of the non-equivalent control group design (Quasi Eksperimental Design bentuk Non-equivalent Control Group Design).Conducting this research in Franjasila Secondary School. The results of the profit calculation from this research were